Castration of Dogs Using Local Anesthesia After Sedating With Xylazine and Subanesthetic Doses of Ketamine - Silva, Erika; Schumacher, John; Passler, Thomas (Frontiers in Veterinary Science, 2020)
Orchectomy is performed in some species using only using sedation and local anesthesia to decrease the expense and inherent danger of performing the procedure using general anesthesia. The objective of this study was to determinine if dogs can be castrated painlessly by using only sedation and local anesthesia. After dogs were sedated with intramuscularly administered xylazine (1 mg/kg) and subanesthetic ketamine HCL (1 mg/kg), testes and skin were anesthetized with buffed 2% lidocaine (6 mg/kg, total dose). Systolic, diastolic, and mean blood pressures; heart and respiratory rates; and movement scores were determined before, and during surgery when manipulations were most likely to cause pain. No dog reacted significantly to injection of the combination of sedatives, and no dog reacted noticeably to injection of lidocaine. During surgery, the average heart rate was reduced from baseline by 40 – 60 beats per minute, and the average respiratory rate was reduced by approximately 10 breaths per minute. An overall reduction of arterial blood pressures was observed. All but one dog moved purposely in response to a toe pinch at the end of surgery. We found that sedating dogs intramuscularly with xylazine and a sub-anesthetic dose of ketamine HCL and administering lidocaine at the incision site and intratesticularly allowed dogs to be castrated humanely and avoided the expense and complications of general anesthesia and the need for hospitalization.